Reviewing Salinity Issues of the Sundarban Mangrove in the Light of Socio-eEnvironmental Implications and Present Initiatives - Saha, Sanjit Kumar (Indian Forester, 2024)
The livelihood, culture and socio-economy of the people residing in the villages surrounding Sundarban of mainly South-24-Parganas and areas of North-24-Parnas District of West Bengal are totally dependent upon Sundarban Mangrove. Actually, Sundarban Mangrove is providing suitable habitat for numerous floras and faunas particular to this region. The regeneration and growth of Mangrove species is totally dependent upon the balancing act of downward movement of fresh water from Rivers and upward movement of tidal saline waters in the Sundarban estuary and delta. But In present situation due to natural and anthropogenic reasons Salinity level in Indian part of Sundarban Mangrove is increasing than the optimum level and affecting the growth of main fresh water loving indicator species of this area viz. Sundari, Goalpata, Keora, etc., and thus affecting the availability of ecosystem goods and services like protection from storm, fishing, honey collection, etc., to the local people in and around the Sundarban Mangrove. Here the study highlights the mitigation measures to address the salinity Issues of the Sundarban.